Reformasi sistem peradilan : sistem penegakan hukum di Indonesia - Arief, Barda Nawawi, 1943- (Semarang : Badan Penerbit, Universitas Diponegoro, 2011)
Reform of the Indonesian courts system.
Includes bibliographical references (p. 82-84).
Keywords: Law reform -- Indonesia; Courts -- Indonesia; Justice, Administration of -- Indonesia